Kajian Penggunaan Media Sosial Instagram sebagai Media Promosi Pariwisata di Desa Aan, Klungkung - Sari, Retno Juwita; Pracintya, Ida Ayu Etsa; Aditya, I Wayan Putra (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
Various kinds of social media platforms are starting to develop in the current era of digitalization, one of which is Instagram social media. This platform can share various forms of uploads in the form of reels, stories, and photos. Through the use of Instagram social media, one of the industries that makes promotion easier is the tourism sector. Aan Tourism Village has various potentials and attractions that can be offered to tourists, ranging from natural, cultural, and educational tourism. Instagram was chosen as the social media used to promote the tourist attractions of the village through the account @dewi.aan2021. This research aims to find out how the social media Instagram @dewi.aan2021 is used to promote its tourist attractions. The research method used was descriptive qualitative, by analyzing the content on the official Instagram account of Aan Tourism Village, Klungkung. The results of this research explained that optimizing the use of Instagram social media can increase the audience reach for each uploaded content on the official Instagram account of Aan Tourism Village through content regarding tourist attractions and activities in the village in the form of reels, stories, and photos that are designed attractively and creatively. It is hoped that this research can increase the creation of creative content to attract awareness of Aan Tourism Village, to Gen-Z and Millennial users who are the largest users on this platform. Keywords: tourist villages, social media, instagram, promotions